Bone turnover markers in gingival crevicular fluid and blood serum of patients with fixed orthodontic appliances. (8th December 2021) - Kloukos, Dimitrios; Mavrogonatou, Eleni; Kletsas, Dimitris; Makras, Polyzois; Koukos, George; Stavropoulos, Andreas; Katsaros, Christos
Summary: Aim: Bone remodelling can be followed through the bone turnover markers (BTMs). Aim of the present study was to record the fluctuation of an osteoclastic and an osteoblastic BTM [C-terminal telopeptide of type I collagen (CTX) and N-terminal pro-peptide of type I pro-collagen (PINP), respectively] in both the gingival crevicular fluid (GCF) and the serum of orthodontic patients before and after the initial application of orthodontic forces. Materials and methods: Twenty-one Caucasian patients were prospectively evaluated. GCF and blood samples were collected in order to measure the selected biomarkers by ELISA at three time-points: exactly before, 5 days, and 14 days after bonding of the appliances. Standardized sample handling and patient preparation procedures were adopted in order to reduce pre-analytical variability. Results: GCF and serum CTX levels were found to be independent of age, although higher in the serum of female subjects. PINP levels were found higher in the serum of patients ≥25 years old, as well as in the GCF of males. A positive correlation between serum and GCF baseline PINP levels was observed. Limitations: The effect of orthodontic treatment on bone remodelling might not be absolutely representative of the local bone microenvironment as the levels of the specific BTMs where measured within the GCF of the lower front teeth. Conclusions: This is the first time PINP and CTX have been evaluated in the GCF and serum of orthodontic patients with fixed appliances. No statistically significant alterations of CTX and PINP levels in the GCF and the serum of patients were recorded over time during the initial stages of orthodontic treatment.